Frequency of Malaria in Children with Fever Without Localizing Sign in Age Less Than 36 Months - Ibrahim, Muhammad; Khan, Afzal (Indus Journal of Bioscience Research, 2025)
Background: Malaria remains a significant cause of fever in children in malaria-endemic regions, particularly in those presenting with fever without localizing signs. Early and accurate diagnosis is essential for timely intervention and effective treatment, but diagnostic challenges persist in resource-limited settings. Objective: To assess the prevalence of malaria in children aged 1 to 36 months presenting with fever without localizing signs. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from February 2024 to August 2024 at the Pediatrics Department, Lady Reading Hospital (LRH), Peshawar. Methodology: A total of 121 children, aged 1 to 36 months, with fever (≥38°C) and no apparent localizing signs were enrolled. A 3 mL blood sample was taken for Giemsa-stained blood smear microscopy to detect malaria parasites. Demographic data, including age, gender, family history of malaria, and socioeconomic status, were recorded. Results: The study included 121 children, with a mean age of 20.0 ± 9.52 months. The prevalence of malaria was found to be 14%, with 17 children testing positive. Stratified analysis revealed no significant associations with age, gender, weight, socioeconomic status, or residential area, but a significant correlation was observed with a family history of malaria (p = 0.000). Conclusion: This study confirms malaria as a common cause of fever in children under 36 months in high-endemic areas. Despite coexisting infections, malaria remains a key concern. We emphasize the diagnostic challenge, highlighting the need for comprehensive strategies and awareness to ensure timely, accurate diagnosis and effective treatment of febrile illness in children.